The Effect of the Hydrophilic and Hydrophobic Behavior of Polymeric Fibers on Some Properties of Reactive Powder Concrete - Al-Mulla, Ikram Faraoun; Al-Rihimy, Ammar Sabah (Engineering, Technology & Applied Science Research, 2025)
This study compares the interface bonding properties of Polyvinyl Alcohol (PVA) fibers and Polypropylene (PP) fibers with a Reactive Powder Concrete (RPC) matrix. The chemical composition and microstructure of the reaction were characterized using Scanning Electron Microscopy (SEM) to understand the influence of PVA and PP fibers on their surrounding matrix. The Interfacial Transition Zone (ITZ) between the fibers and the RPC matrix was examined in detail. The hydrophilic and hydrophobic behavior of PVA and PP fibers affected the tensile strain capacity and flexural strength properties of the concrete mixes. Two strength grades of RPC mixes were used (30 MPa and 60 MPa, both with 1% fiber content of PVA or PP). The PVA fibers showed superior bonding with the RPC matrix compared to the PP fibers. The 60 MPa PVA mix achieved the highest strain capacity of 13.8%. The 30 MPa PVA mix had a maximum flexural strength enhancement of 4.3%, while the 60 MPa PVA mix demonstrated a 23% increase. Such enhancement can broaden the use of RPC with PVA fibers in structural members subjected to tensile and flexural stresses, while its significant strain capacity lessens the likelihood of microcrack formation.